Extremely low birth weight (ELBW) neonates for emergency surgery- A challenge for the Anesthesiologist: A case series - Preeti Goyal Varshney; Madhurima Sinharay; Anshu Gupta; Maitree Pandey (EL-Med-Pub, 2024)
Background: Extremely Low Birth Weight (ELBW) newborns, defined as those with a birth weight of 1000 grams or less, present challenging anesthetic scenarios. Emergency surgeries in these infants elevate their vulnerability to various complications. Case Presentation: We present a case series involving 5 ELBW neonates who underwent emergency surgery. Three of them were at a post-conceptual age (PCA) of ≥ 33 weeks and underwent procedures for congenital birth defects, including esophageal atresia, ileal atresia, and gastroschisis. The remaining two neonates, with a PCA of 29-30 weeks, underwent surgery for necrotizing enterocolitis (NEC). Conclusion: The compromised physiology resulting from distinct disease processes and the underdeveloped systems of ELBW preterm neonates necessitate focused care and strategic anesthesia. This approach is crucial to mitigate morbidity and mortality risks in such vulnerable patients.